Blood interactions with nano- and microfibers: Recent advances, challenges and applications in nano- and microfibrous hemostatic agents. (15th January 2019) - Nakielski, Paweł; Pierini, Filippo
Graphical abstract: Abstract: Nanofibrous materials find a wide range of applications, such as vascular grafts, tissue-engineered scaffolds, or drug delivery systems. This phenomenon can be attributed to almost arbitrary biomaterial modification opportunities created by a multitude of polymers used to form nanofibers, as well as by surface functionalization methods. Among these applications, the hemostatic activity of nanofibrous materials is gaining more and more interest in biomedical research. It is therefore crucial to find both materials and nanofiber structural properties that affect organism responses. The present review critically analyzes the response of blood elements to natural and synthetic polymers, and their blends and composites. Also assessed in this review is the incorporation of pro-coagulative substances or drugs that can decrease bleeding time. The review also discusses the main animal models that were used to assess hemostatic agent safety and effectiveness. Statement of Significance: The paper contains an in-depth review of the most representative studies recently published in the topic of nanofibrous hemostatic agents. The topic evolved from analysis of pristine polymeric nanofibers to multifunctional biomaterials. Furthermore, this study is important because it helps clarify the use of specific blood-biomaterial analysis techniques with emphasis on protein adsorption, thrombogenicity and blood coagulation. The paper should be of interest to the readers of Acta biomaterialia who are curious about the strategies and materials used for the development of multifunctional polymer nanofibers for novel blood-contacting applications.